Legal Implications of Transfer of Land Rights Through a Deed of Sale and Purchase Based on a Letter of Inheritance Which is Not Known to All The Heirs - Ys, Tiara.; Wahyudi, Trubus (Jurnal Konstatering, 2025)
The transfer of land rights is an important aspect of agrarian law that requires legal certainty for the parties involved. However, in practice, it is common to find deeds of sale and purchase made based on inheritance letters that are not known to all heirs, thus giving rise to legal issues related to the validity and legal consequences of the transfer of rights. This study aims to analyze the legal implications of the transfer of land rights through deeds of sale and purchase based on inheritance letters that do not involve all heirs. The research method used is a normative juridical approach with literature studies as the main data source. The results of the study indicate that deeds of sale and purchase made based on inheritance letters without the consent of all heirs can result in the deed being null and void and give rise to land rights disputes in the future. In addition, this kind of transfer of rights has the potential to harm other heirs and the buyer who has already made the transaction. Therefore, compliance with the principle of deliberation and mutual agreement of all heirs is necessary in the preparation of inheritance letters and transfer of rights to create legal certainty and protection for all interested parties. These legal implications emphasize the importance of protecting inheritance rights in land sale and purchase transactions to prevent legal conflicts in the future.